EFEK PAPARAN ASAP BIOMASSA GAMBUT TERHADAP STRESS OKSIDATIF PADA TIKUS WISTAR - Uly Astuti Siregar Uly Astuti Siregar; May Valzon; Fitrianti; Arif Budianto (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: Indonesia ranks third in the world regarding air pollution due to forest and land fires; most of the land burned is a peatland. Particulate matter (PM) 2.5 is the largest component of the total smoke particles. Short-term and long-term exposure to PM2.5 remains a hazard to human health.Objective: This study aims to examine the effect of exposure to peat biomass smoke on serum malondialdehyde (MDA) levels and body weight of Wistar rats.Methods: Experimental animals were randomly divided into three groups: Control group (C) is not given treatment, and treatment groups (X1 and X2) are exposed to smoke from peat biomass of 100 g and 150 g of biomass for 60 seconds per day for 14 days. The body weight was examined before and after treatment, while Serum MDA levels were examined after treatment.Results: The results showed significant differences (p < 0.05) in serum MDA levels between groups. The highest serum MDA levels were found in group X2 (3.03 ± 0.185 nmol/ml), followed by group X1 (2.67 ± 0.212 nmol/ml) compared to the control group (2.24 ± 0.476 nmol/ml). In contrast, increasing body weight between groups did not show a significant difference.Conclusion: Exposure to PM 2.5 from peat biomass smoke increases oxidative stress in experimental animals.